Optimizing Manhour Productivity in Automotive Component Packing Process Using the ECRS Approach - Ahmad Fauzi; Faqih Sidik Muttaqin; Muhammad Asyraf Hisyam Hidayat; Setiawan Laia; Yudi Prastyo (Lentera Ilmu Nusantara, 2026)
This study aims to improve manhour productivity in the packing process of an Indonesian automotive component company by applying the ECRS method (Eliminate, Combine, Rearrange, Simplify). The problem was identified from low labor productivity caused by non-value-added activities, inefficient work layout, non-ergonomic material placement, and the absence of proper work aids. A quantitative approach was used through direct observation, time study, motion analysis, fishbone diagram, and operation process chart to identify waste and determine improvement actions. The implementation of ECRS reduced the cycle time from 60 seconds to 46 seconds per unit, representing a 23.3% improvement, and increased output from 60 units/hour to 78 units/hour, equivalent to a 30% productivity increase. In addition, the improvement eliminated unnecessary movements, simplified work procedures, and enhanced ergonomic conditions for operators. The findings indicate that the ECRS approach provides a practical contribution to improving efficiency in manual packing processes without adding labor or major production equipment. Therefore, this method can be used as an effective and low-cost improvement strategy for productivity enhancement in manufacturing operations.